Evaluating sulfurization as a blue carbon sink in a southern California salt marsh - Lena R. Capece; Melea Bailey; Max Morrison; Alexandra A. Phillips; Lewis Sharpnack; Sam M. Webb; Dana C. Brenner; Maya Gomes; Morgan R. Raven (Limnology and Oceanography, 2025)
Blue carbon ecosystems such as seagrass meadows, mangrove forests, and salt marshes are important carbon sinks that can store carbon for millennia. Recently, organic matter sulfurization and pyritization have been proposed as mechanisms of net carbon storage in blue carbon ecosystems. At our study site, organic sulfur that is resistant to acid hydrolysis (protokerogen) is an order of magnitude less abundant than pyrite sulfur, suggesting a dominance of pyritization over sulfurization. The C/N ratios and carbon isotope compositions suggest that nearly half of total organic carbon and ≥ 80% of protokerogen is composed of marsh plant material. Sediment protokerogen appears to be sulfurized based on its low δ 34 S values (− 10‰), abundance of disulfides, and higher S/C ratio (~ 1.0%) relative to potential biogenic sulfur sources. However, the interpretation of protokerogen δ 34 S values is complicated by the wide range in sulfur isotope compositions of marsh plants. Evidence for sulfurization occurs within the shallowest sediments across different vegetation zones, yielding consistent products, while pyritization appears to be more sensitive to alterations in sediment redox conditions. Based on organic sulfur and pyrite content, sulfurization may be a more spatially consistent process than pyritization, with implications for carbon storage. The relative abundance of pyrite and protokerogen organic sulfur indicates that pyritization is favored at our study site, but this is likely to vary across the spectrum of blue carbon ecosystems.

Organic sulfur from source to sink in low‐sulfate Lake Superior - Alexandra A. Phillips; Imanol Ulloa; Emily Hyde; Julia Agnich; Lewis Sharpnack; Katherine G. O'Malley; Samuel M. Webb; Kathryn M. Schreiner; Cody S. Sheik; Sergei Katsev; Morgan Reed Raven (Limnology and Oceanography, 2023)
Organic sulfur plays a crucial role in the biogeochemistry of aquatic sediments, especially in low sulfate ( μ M) environments like freshwater lakes and the Earth's early oceans. To better understand organic sulfur cycling in these systems, we followed organic sulfur in the sulfate‐poor ( μ M) iron‐rich (30–80 μ M) sediments of Lake Superior from source to sink. We identified microbial populations with shotgun metagenomic sequencing and characterized geochemical species in porewater and solid phases. In anoxic sediments, we found an active sulfur cycle fueled primarily by oxidized organic sulfur. Sediment incubations indicated a microbial capacity to hydrolyze sulfonates, sulfate esters, and sulfonic acids to sulfate. Gene abundances for dissimilatory sulfate reduction ( dsrAB ) increased with depth and coincided with sulfide maxima. Despite these indicators of sulfide formation, sulfide concentrations remain low (